Synthesis and characterization of polyacids from palm acid oil and sunflower oil via addition reaction - Zeimaran, E.; Kadir, M.R.; Nor, H.M.; Kamarul, Tunku; Djordjevic, I. (Elsevier, 2013)
In this study aliphatic polyacids were synthesized using palm acid oil (PAO) and sunflower oil (SFO) via addition reaction technique. The synthesized materials were characterized using Fourier-transform infra-red (FTIR) spectroscopy, nuclear magnetic resonance (NMR) spectroscopy, matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-ToF-MS) and thermo-gravimetric analysis (TGA). Mixing formic acid and hydrogen peroxide with PAO or SFO at the ratio 3:10:1 produced the lowest iodine value of 10.57 and 9.24 respectively, indicating the increase in epoxidization of both oils. Adding adipic acid to the epoxidized oils at a ratio of 1:10 increases the acid values of SFO and PAO to 11.22 and 6.73 respectively. The existence of multi-acid groups present in synthesized polyacid was confirmed by MALD-ToF-MS. This feature indicates a possible value to the biomaterials development.